Cystic rectal duplication in infants: A case report and review of literature - Gupta Vipul; Sharma Shyam (Wolters Kluwer Medknow Publications, 2006)
Rectal duplication is described in a 1-month-old male infant who presented with constipation for the last 5 days. A presence of a cystic mass in relation to posterior wall of rectum revealed on clinical and radiological examination provided a clue to diagnosis. The clinical presentations and the management protocol of this rare entity are discussed. Authors review their experience with this rare entity and the pertinent literature.